Dyslipidemia and diabetes mellitus: Role of lipoprotein species and interrelated pathways of lipid metabolism in diabetes mellitus. (December 2021) - Kane, John P.; Pullinger, Clive R.; Goldfine, Ira D.; Malloy, Mary J.
Abstract: Diabetes mellitus is a complex disease. We are increasingly gaining a better understanding of its mechanisms at the molecular level. From these new insights, better therapeutic approaches should emerge. Diabetes mellitus is a syndrome with many associated subphenotypes. These include mitochondrial disorders, lipodystrophies, and inflammatory disorders involving cytokines. Levels of sphingosine-1-phosphate, which has recently been shown to play a role in glucose homeostasis, are low in diabetics, whereas levels of ceramides are increased. Major phenotypes associated with diabetes mellitus are dyslipidemias, notably hypertriglyceridemia and low high-density lipoprotein cholesterol levels. Both diabetes and dyslipidemia are strongly associated with increased risk for atherosclerotic vascular disease.